2014
DOI: 10.1097/sla.0000000000000339
|View full text |Cite
|
Sign up to set email alerts
|

A Multisite Randomized Controlled Trial of Brief Intervention to Reduce Drinking in the Trauma Care Setting

Abstract: Objective Determine the efficacy of three brief intervention strategies that address heavy drinking among injured patients. Summary of Background Data The content or structure of brief interventions most effective at reducing alcohol misuse following traumatic injury is not known. Methods Injured patients from three trauma centers were screened for heavy drinking and randomly assigned to brief advice or BA (n=200), brief motivational intervention or BMI (n=203), or brief motivational intervention plus a te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 36 publications
1
65
0
Order By: Relevance
“…Brief interventions using MI appear to be generally effective in trauma center, emergency department, medical inpatient, and primary care general medical settings, although treatment effects vary across settings and patient populations (Bertholet, Palfai, Gaume, Daeppen, & Saitz, 2014; Bray, Cowell, & Hinde, 2011; Cunningham et al, 2009; D’Onofrio et al, 2012; D’Onofrio et al, 2010; Field, Baird, Saitz, Caetano, & Monti, 2010; Havard, Shakeshaft, & Sanson-Fisher, 2008; Jonas et al, 2012; Madras et al, 2009; Nilsen et al, 2008; Vasilaki, Hosier, & Cox, 2006; Whitlock, Polen, Green, Orleans, & Klein, 2004). More specifically, with injured patients admitted to trauma centers, brief interventions using MI have been shown to improve alcohol use problems (Field et al, 2014; Field, Caetano, Harris, Frankowski, & Roudsari, 2010; Gentilello et al, 1999; Schermer, Moyers, Miller, & Bloomfield, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…Brief interventions using MI appear to be generally effective in trauma center, emergency department, medical inpatient, and primary care general medical settings, although treatment effects vary across settings and patient populations (Bertholet, Palfai, Gaume, Daeppen, & Saitz, 2014; Bray, Cowell, & Hinde, 2011; Cunningham et al, 2009; D’Onofrio et al, 2012; D’Onofrio et al, 2010; Field, Baird, Saitz, Caetano, & Monti, 2010; Havard, Shakeshaft, & Sanson-Fisher, 2008; Jonas et al, 2012; Madras et al, 2009; Nilsen et al, 2008; Vasilaki, Hosier, & Cox, 2006; Whitlock, Polen, Green, Orleans, & Klein, 2004). More specifically, with injured patients admitted to trauma centers, brief interventions using MI have been shown to improve alcohol use problems (Field et al, 2014; Field, Caetano, Harris, Frankowski, & Roudsari, 2010; Gentilello et al, 1999; Schermer, Moyers, Miller, & Bloomfield, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…Screening methods, patient recruitment, study design and intervention, and rates of follow-up have been reported in detail previously 19. Patients who agreed to participate completed a baseline (BL) assessment that captured socio-demographics, alcohol use severity and injury-related risk behaviour.…”
Section: Methodsmentioning
confidence: 99%
“…Eight indicators were selected from the Short Inventory of Problems+6 (SIP+6)19 23 based on their previously demonstrated relationship with individuals seeking emergency and trauma care3 6 24 and our previous work of identifying injured patient profiles associated with alcohol use 17 18. These items include (1) having driven a motor vehicle after having three or more drinks; (2) having taken foolish risks while drinking; (3) having gotten into a physical fight while drinking; (4) having been arrested for driving under the influence of alcohol; (5) having had trouble with the law (other than driving while intoxicated) because of drinking; (6) having had an accident while drinking or intoxicated; (7) having been physically hurt, injured or burned while drinking or intoxicated; and (8) having injured someone else while drinking or intoxicated.…”
Section: Methodsmentioning
confidence: 99%
“…Korcha, Cherpitel, Moskalewicz, Bond, and Ma (2012) found brief interventions motivate patients to decrease alcohol consumption and realize the connection of drinking and the occurrence of physical or social problems. Brief interventions have been proven to be more effective if a follow-up contact is made to reinforce changes in alcohol intake ( Field et al, 2014 ). Success in getting patients to agree to follow-up is contingent on the manner in which the brief intervention is performed.…”
mentioning
confidence: 97%